Restricted CD4+ T cell receptor repertoire impairs cognitive function via alteration of Th2 cytokine levels. Issue 1 (1st January 2017) - Song, Eun Ji; Jeon, Seong Gak; Kim, Kyoung Ah; Kim, Jin-il; Moon, Minho
ABSTRACT: Despite the effects of CD4+ T cell dysfunction on cognitive and behavioral impairment are well established, the effects of Th2 cytokines on the adult hippocampal neurogenesis and cognitive function in restricted CD4+ T cell receptor (TCR) repertoire model have not been fully elucidate. We found that mice with restricted CD4+ repertoire TCR showed decreased adult hippocampal neurogenesis using OT-II mice. Moreover, we demonstrated that OT-II mice showed increased Th2 cytokine levels in peripheral organs and IL-4 levels in brain. Taken together, altered Th2 cytokine levels may impact learning and memory via impaired adult neurogenesis in restricted CD4+ repertoire TCR mice.